1999
DOI: 10.1074/jbc.274.8.5061
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Neuronal Cells from Apoptosis by Hsp27 Delivered with a Herpes Simplex Virus-based Vector

Abstract: Overexpression of the gene encoding the 70-kDa heat shock protein (hsp70) has previously been shown to protect neuronal cells against subsequent thermal or ischemic stress. It has no protective effect, however, against stimuli that induce apoptosis, although a mild heat shock (sufficient to induce hsp synthesis) does have a protective effect against apoptosis. We have prepared disabled herpes simplex virus-based vectors that are able to produce high level expression of individual hsps in infected neuronal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
128
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(135 citation statements)
references
References 50 publications
6
128
0
1
Order By: Relevance
“…6 Hsp27 is highly expressed in neuronal cells and is shown to protect against neuronal cell apoptosis. 7 Mehlen et al 8 reported an increase in Hsp27 expression and Hsp27-dependent protection against apoptosis during dopamine-induced, cAMP-dependent differentiation of rat olfactory neuroblasts. Since there are direct parallels between survival and differentiation in these two experimental systems, we hypothesised that Hsp27 may represent a downstream target of the Brn3a transcription factor during neuronal cell survival and differentiation.…”
Section: Dear Editormentioning
confidence: 99%
“…6 Hsp27 is highly expressed in neuronal cells and is shown to protect against neuronal cell apoptosis. 7 Mehlen et al 8 reported an increase in Hsp27 expression and Hsp27-dependent protection against apoptosis during dopamine-induced, cAMP-dependent differentiation of rat olfactory neuroblasts. Since there are direct parallels between survival and differentiation in these two experimental systems, we hypothesised that Hsp27 may represent a downstream target of the Brn3a transcription factor during neuronal cell survival and differentiation.…”
Section: Dear Editormentioning
confidence: 99%
“…Its proapoptotic ability can be inhibited by Bcl-2 and Bcl-X L . 38 Another important group of apoptosis regulators are heatshock proteins that include alpha-crystallins (a-crystallins), [39][40][41][42][43][44][45][46] Hsp27, [39][40][47][48][49][50][51][52] Hsp70, [53][54][55][56][57] Hsp90 58 and Hsp60. [59][60] While Hsp60 appears to enhance apoptosis by promoting maturation of procaspase-3, 59,60 the majority of these factors seems to protect cells from induced apoptosis through different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Induction of Hsps on exposure to a stressor confers protection against exposure to a subsequent stressor in various cell types (29,30). Overexpression of individual Hsps also protects against thermal and ischemic stress and apoptosis (31,32). Hsps may also regulate stress-responsive signaling pathways such as activation of c-Jun N-terminal kinase1 (JNK1) and p38 (33).…”
mentioning
confidence: 99%